Virunum (Magdalensberg) – prospects for research on Roman provincial cities - Kaczmarek, Zofia (Balcanica Posnaniensia. Acta et studia, 2025)
The Roman Empire is one of the most important phenomena in the history of Europe. For several centuries, it expanded largely undisturbed, and its cities, built on its frontiers, not only testified to its greatness but also served as a guarantee of the enduring nature of Roman ideals. This study investigates the processes of Romanization and urban development in the settlements of Magdalensberg and Virunum, Carinthia, Austria. It is based on an interdisciplinary approach combining archaeological, epigraphic, and historical analysis to reconstruct the chronology and character of urban development. Moreover, architectural remains, inscriptions, and material culture are examined to assess the mechanisms of Roman cultural transmission and local adaptation. The findings indicate that Romanization in Noricum predated formal annexation and was initially stimulated by commercial and cultural exchange with Aquileia. Magdalensberg emerged as a center reflecting Italian architectural models, while the foundation of Virunum under Claudius represented the full institutional and spatial integration of the province. The evidence reveals a dynamic process of cultural negotiation that produces a provincial identity. And since the Roman culture lies at the foundations of modern Europe, the research into the Roman cities of the North-West has a significant impact on the broader study of European history